COMPARATIVE ANALYSIS OF THE RECOVERY TIME OF THE INVESTMENT IN THERMAL SOLAR COLLECTORS IN THE ARGENTINE REPUBLIC THROUGH GEOGRAPHIC INFORMATION SYSTEMS (Journal of Industrial and Mechanical Engineering, 2022)
The growth of the solar thermal market, both worldwide and in Argentina, has generated an increase in imports and local production of various solar thermal collectors with highly heterogeneous characteristics.The extension of the Argentine territory presents a great amplitude of temperature and solar radiation, these are the main variables that affect the performance and energy production of solar collectors.This work analyzes the return on investment time (RIT) of 2 typical solar collectors, flat plate and vacuum tube, for average ambient temperature and radiation values, compared to a traditional efficiency "A", hot water tank operating at natural gas and electric resistance.Determining how the RIT of both collectors vary, to then make maps of the Argentine Republic through Geographic Information Systems (GIS) that show how the RIT varies in years throughout the territory for the conditions mentioned above.
Keywords: GIS; invesment; collector; solar; Argentine